Clear aligners, the aesthetic solution: a review - Ganta, Gopala Krishna; Cheruvu, Kamala; Ravi, Rama Krishna; Reddy, Raghavendra Prasad (International Journal of Dental Materials, 2021)
In the recent past, the demand for adult orthodontic treatment has increased multiple folds. As a repercussion of this stipulation, invisible orthodontic treatment has expanded its horizon. Efforts of using aesthetic brackets, wires, and lingual techniques to meet the expectations of adult patients have been practised. Though these techniques seemed to be promising in the initial days, soon decreased in popularity due to drawbacks associated with them. Clear aligners were offered as a newer and superior aesthetic alternative to overcome the difficulties associated with prior aesthetic approaches. These aligners are made up of different thermoplastic materials intended to move the malpositioned teeth in the desired corrected position following push mechanics. This article deals with new generation orthodontic treatment using aligners. It deals with history, generations, different materials used, and the distances yet to be travelled to become the benchmark and replace the existing conventional braces. This paper also gives a bird’s eye view of the method of aligner fabrication and the significant differences between the regular braces and aligners used in orthodontics.